Changing trends in rectal prolapse management in a tertiary care hospital - Joshi, Arbin (Journal of Patan Academy of Health Sciences, 2017)
Introductions: Optimum operation for rectal prolapse is not established yet. Laparoscopic procedures are gaining popularity and on the other hand, proponents of perineal procedures are also not scarce.Methods: Rectal prolapse cases operated during five years in a tertiary care hospital regarding immediate post-surgical outcome of abdominal and perineal procedures were reviewed.Results: Total 30 patients of rectal prolapse were operated during the study period. Over the years, Altemiere's rectosigmoidectomy outnumbered abdominal procedures. Immediate postoperative complications were similar except for one case in perineal group needing laparotomy for intraperitoneal bleed.Conclusions: Altemiere's rectosigmoidectomy was safe and increasingly acceptable procedure at our center for patients with rectal prolapse.